LOVE IS THE CLEANSING POWER - M.K. Mukhiddinov (International Journal of Advanced Science and Technology, 2020)
This view is known as the mystic philosophy of mysticism. According to this philosophy, since the universe is a mirror of the deity, movement and activity are reflected by the reflection of light in the mirror, and the ultimate end of the world is the human soul. That is why the human soul seeks its origin, that is, to the presence of God, and it is through the authority of the teaching or it is obtained by love. Thus love is one of the qualities of a perfect man. Man is born with love and is full of knowledge. Navoi did not deny intelligence, knowledge, skills and experience for human perfection. Mind and knowledge are necessary to man, but the secret of the divine secret is attained by love. This is the conclusion that comes from the irrelevant worldview of mysticism. God gave love, and love covered the whole world. Because there has always been love for beauty. Love and love are among the topics covered in the works of Nizami, Khusrav Delhi and Alisher Navoi. Already, this theme is central to the works of all Sufi poets, such as Farididdin Attor, Mevlana Rumi, Saadi Sherozi, Khoja Hafiz Sherozi, Mavlono Lutfi, and Abdurahmon Jomi. This should not be a surprise.